2006
DOI: 10.1111/j.1472-8206.2006.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of gentamicin‐induced renal dysfunction and injury by the phenolic extract of soybean (Glycine max)

Abstract: Gentamicin (GM) is one of the most important of the aminoglycoside antibiotics used widely for the treatment of serious and life-threatening infections and whose clinical use is limited by its nephrotoxicity. As the pathogenesis of GM-induced renal dysfunction and injury involves reactive oxygen species, the polyphenolic constituents of soybean with antioxidant property may protect against GM-induced renal toxicity. We therefore tested this hypothesis using phenolic extract of soybean (PESB) on GM-induced neph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Similarly, malondialdehyde (an important by-product and useful index of lipid peroxidation) level in the BSC-treated rats was also not significantly different from control. While several authors have demonstrated similar observation with many established antioxidant herbal or medicinal plants in normal animals or animals without oxidative stress-mediated pathologies, 60 , 61 , 62 further studies will be required to establish the direct antioxidant potential or otherwise of BSC in conditions of oxidative tissue/organ dysfunction or damage.…”
Section: Discussionmentioning
confidence: 63%
“…Similarly, malondialdehyde (an important by-product and useful index of lipid peroxidation) level in the BSC-treated rats was also not significantly different from control. While several authors have demonstrated similar observation with many established antioxidant herbal or medicinal plants in normal animals or animals without oxidative stress-mediated pathologies, 60 , 61 , 62 further studies will be required to establish the direct antioxidant potential or otherwise of BSC in conditions of oxidative tissue/organ dysfunction or damage.…”
Section: Discussionmentioning
confidence: 63%
“…γ‐GT is an enzyme localized in the cell membrane of many cell types including renal tubular cells and in the ER of hepatocytes [40]. In fact, the kidney has the highest γ‐GT activity in several mammals studied, including humans [34]. Many GSH‐conjugates undergo further enzymatic modification by hydrolysis of the glutathione‐ S ‐conjugate at the γ‐glutamyl bond, a reaction which is catalyzed by the enzyme γ‐GT.…”
Section: Discussionmentioning
confidence: 99%
“…In the reviewed reports, it was shown that soybean seeds are an important source of dietary tocopherols, but like the seeds of other dicotyledonous plants, they contain relatively little alpha‐tocopherol, the form with the greatest vitamin E activity (Britz & Kremer, 2002; Yoshida et al ., 2006). In all probability, the obtained relatively high value of antioxidant activity of soybean in this report mostly relates to its polyphenol content (Takahashi et al ., 2005; Ekor et al ., 2006).…”
Section: Discussionmentioning
confidence: 99%